How does school spending per pupil differ across the UK? - Luke Sibieta (Institute for Fiscal Studies (IFS), 2023)
Given that education policy is a devolved matter across the UK, a natural question to ask is how school spending per pupil differs across the four nations of the UK. In this short report, we show how school spending per pupil has changed across the four nations of the UK over time. We also directly show how the level of COVID-related spending on schools differed across the four nations of the UK. To ensure consistent comparisons, our measure of school spending relates to spending on the early years, schools and school sixth forms per pupil aged 3-19 attending these settings in each nation.
Keywords: 330; Education and skills; Government finances and spending; Education spending; COVID-19; Devolution; Devolved government finances; Education; Geography; Government spending; Northern Ireland; Public sector; Schools; Scotland; Wales